Management of BNT162b2 mRNA COVID-19 vaccine in children aged 5-11 years with allergies, asthma, and immunodeficiency: consensus of the Italian Society of Pediatric Allergy and Immunology (SIAIP) - Elio Novembre; Mariangela Tosca; Carlo Caffarelli; Mauro Calvani; Fabio Cardinale; Riccardo Castagnoli; Elena Chiappini; Claudio Cravidi; Michele Miraglia Del Giudice; Marzia Duse; Amelia Licari; Sara Manti; et al. (BMC, 2022)
Abstract BNT162b2 vaccine, developed by BioNTech and Pfizer ha recently approved for use in children aged 5 to 11 years. Recent data show evidence of safety on the administration and serious adverse events have been rarely reported. However, allergic systemic reactions could occur. In some cases, a correct allergic evaluation allows identifying patients at risk of developing an anaphylactic reaction. Risk assessment of allergic reactions to COVID-19 vaccines is useful to limit contraindications to vaccination and help to safely vaccinate people supposed to be at risk of allergic reactions.